2021
DOI: 10.2174/1871526521666210222125215
|View full text |Cite
|
Sign up to set email alerts
|

Serratia, No Longer an Uncommon Opportunistic Pathogen – Case Series & Review of Literature

Abstract: Background: Serratia spp. is a common enteric bacterium generally thought not to be pathogenic in the gastrointestinal tract. Serratia marcescens is a member of the genus Serratia, which is a part of the family Enterobacteriales..Of all Serratia species, S. marcescens is the most common clinical isolate and the most important human pathogen. Objective: We are discussing here four cases of Serratia marcescens which we reported in our laboratory in the Department of Microbiology Government Medical College and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Earlier studies have identified Lachnoclostridium to be significantly enriched in the fecal samples of colitis [ 19 ], colitis-associated colorectal cancer [ 20 ] in mice, and as a potential marker in adenoma patients [ 21 ]. Moreover, Acinetobacter is enriched in actively inflamed colitis tissue [ 22 ] and Serratia has been long reported as an opportunistic pathogen [ 23 ]. Our results also showed that the RSV group had an increased abundance of ‘beneficial’ genera such as Rikenellaceae RC9 gut group, Ruminococcaceae NK4A214 group, Ruminococcaceae UCG-005, Ruminiclostridium 5, and [Eubacterium] fissicatena group compared with the NC group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have identified Lachnoclostridium to be significantly enriched in the fecal samples of colitis [ 19 ], colitis-associated colorectal cancer [ 20 ] in mice, and as a potential marker in adenoma patients [ 21 ]. Moreover, Acinetobacter is enriched in actively inflamed colitis tissue [ 22 ] and Serratia has been long reported as an opportunistic pathogen [ 23 ]. Our results also showed that the RSV group had an increased abundance of ‘beneficial’ genera such as Rikenellaceae RC9 gut group, Ruminococcaceae NK4A214 group, Ruminococcaceae UCG-005, Ruminiclostridium 5, and [Eubacterium] fissicatena group compared with the NC group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria of the genus Serratia are ubiquitous and have been isolated from soil, water, plant roots, insects, and the gastrointestinal tract of animals (Cristina et al, 2019; Gupta et al, 2021; Lo et al, 2016). This broad range of environments exposes Serratia strains to exogenous genetic elements such as plasmids, phages, and chromosomal fragments of other bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Serratia , a Gram‐negative rod, is now part of the family Yersiniaceae . Serratia species can be found in different environments (e.g., water, soil) and hosts (e.g., humans, insects, plants, vertebrates) where they may play different roles ranging from opportunistic pathogens to symbionts (Cristina et al, 2019; Gupta et al, 2021; Lo et al, 2016). Among Serratia species, marcescens is undoubtedly the most studied mainly for its role played as a symbiont associated with insects and nematodes (Chen et al, 2017) or as a human opportunistic pathogen (currently reported as one of the most important bacteria responsible for acquired hospital infections such as bacteremia, pneumonia, intravenous catheter‐associated infections, and endocarditis) (Ferreira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant in the environment, Serratia marcescens is an opportunistic pathogen that frequently causes hospital-acquired infections, particularly catheter-associated bacteremia and urinary tract infections, as well as wound infections. Antibiotic-resistant strains are common, making phage therapy a possible alternative treatment ( 1 , 2 ). The isolation, complete genome sequences, and annotation of 14 Serratia siphophages are presented.…”
Section: Announcementmentioning
confidence: 99%